PENGARUH MENDENGARKAN AL-QUR’AN DAN MUSIK KLASIK TERHADAP PENURUNAN TEKANAN DARAH PADA MASYARAKAT RT 05 RW 12 KELURAHAN TANGKERANG SELATAN KOTA PEKANBARU TAHUN 2020 - Yuyun Priwahyuni; Christine Vita Gloria Purba; Agus Alamsyah; Ikhtiaruddin Ikhtiaruddin (STIKes Al-Insyirah Pekanbaru, 2020)
ABSTRACT Blood pressure is the pressure contained in the blood vessels that occurs when the heart pumps blood throughout the body. The increase in arteries normally up to 120 mmHg is called systolic pressure which occurs when the heart contracts to pump blood during relaxation wherein the ventricular aortic pressure tends to decrease up to 80 mmHg, which is called diastolic pressure. The prevalence of hypertension in Riau (29.2%) (Riskesdas, 2018). The chanting of the Qur'an contains an element of the human voice, which is a wonderful healing instrument and one of the easiest to reach. Listening to music can also stimulate the hypothalamus, which is the center of regulation of various body mechanisms, so that it affects blood pressure, pulse, respiration, and mood. The results of the survey in RT 05 RW 12 Kelurahan Tangkerang Selatan City of Pekanbaru on 35 people showed that 20 (57%) had blood pressure above 120/80 mmHg. This study aims to determine the effect of listening to the Qur'an and classical music on blood pressure reduction in the community of RT 05 RW 12 Kelurahan Tangkerang Selatan, Pekanbaru City in 2020. This type of analytical research is a quasi experimental design. Population of 20 people with blood pressure above 120/80 mmHg, the sample is the total population. Computerized data processing. The data analysis used was univariate and bivariate analysis with paired t test. There was a decrease in blood pressure in the group listening to the Al-Qur'an and the group listening to classical music, the ratio of decreasing blood pressure in the listening group of the Al-Qur'an was greater, namely 8.7 compared to the group listening to classical music which was 1.7. The significance value (2-tailed) is 0.0001 so that the results of the initial test and the final test experience a significant change (meaning). It is hoped that the head of the RT and its apparatus can coordinate with the local puskesmas to carry out regular blood pressure checks so that degenerative diseases such as hypertension can be controlled. Keywords: blood pressure, murotal Al-Qur'an Surat Al-Rahman, classical music